Rancang bangun aplikasi manajemen sistem pelayanan penyediaan jasa berbasis online - Mesa Abdilah; Verdi Yasin; Akmal Budi Yulianto (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2022)
Service management information system is a part of remote service through internet technology media. Business companies must be able to adapt, if initially the company focused on how to provide direct, quality services, now companies are faced with the fact that to win in the midst of competition, companies must provide online or electronic media which of course must also be of high quality. The process of collecting data using the method of observation, interviews and literature study. In system development using Extreme Programming method. System design tools used are activity diagrams and Use case diagrams. Meanwhile, for the manufacture of an online-based service provider system, the author uses the programming language used is React JS for the front end, Express JS for the back end and PostgreSQL as the database. Based on the results of the study, an online-based service management information system was obtained. The implementation of this service system is made with facilities including service orders, latest repair status information, user data management, payments and transaction history that have been carried out.